Uwagi o przemianach budownictwa drewnianego na przełomie wczesnego i późnego średniowiecza - Gupieniec, Romana (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
Though early medieval and modern architecture, studied by ethnographers, is fairly well known, there is a gap in our knowledge of building in the Late Middle Ages. It was only with the development of historical archaeology, first directed towards the study of defensive features, residential architecture, castles and finally towns that the interest in single constructions or whole architectural complexes began to grow. The studies performed so far show that in the Late Middle Ages three basic constructional types existed side by side: 1) houses with cross joint logs corners (block construction); 2) houses with walls of short timber planks tenoned into the slots of vertical posts; 3) timber-framed houses. For lack of adequate data it is not possible to assess their respective proportions or the preponderance of any of them. Presumably various factors such as character of settlement, natural environment, limitation of timber felling and also regional specificity, already distinct at that time, had played a part. It is also possible to assume that a two-room house with a central entrance lobby began to appear in the early 13th century. It seems that in the Late Middle Ages the importance of block construction (type 1), outstanding in the preceding periods, did not decline, though this type began to disappear relatively early from urban settlement. That period witnessed a sort of revival of the second constructional type only occasional in the Early Middle Ages, but fairly common in prehistoric times. The timber-frame-and-board construction (type 3), recorded in Poland about the mid-13th century, is best documented at Pułtusk. It was inspired by the palisade type called stav – Stabbau, a more developed form of which was earlier known in Germany and Scandinavia. This construction seems to have been employed in late medieval towns and preceded houses built on a timber frame with wattle-and-daub walls, which began to appear only in the 14th-15th centuries. Gdansk, where because of its specificity, houses with brick-nogged timber walls appeared much earlier, is an exception.